Theoretical and methodological foundations of management psychology in the restaurant and hotel business - Ismailova, Р.; Amandosov, А.; Kuzekbaeva, С.; .Kalabaev, А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2024)
This article examines the theoretical and methodological foundations of management psychology in the context of the restaurant and hotel business. Particular attention is paid to such aspects as employee motivation, leadership and emotional intelligence. The article provides an analysis of the main psychological models, including Maslow's and Herzberg's theories of motivation, as well as their practical application to improve team performance and customer satisfaction. Methodological approaches to personnel management are explored, such as the use of employee behavior assessment methods, implementation of training and motivational programs. Various leadership styles and their impact on productivity are considered, as well as ways to adapt them in the hospitality industry. The article emphasizes the importance of using psychological approaches to improve competitiveness and create a positive working atmosphere.